Subclinical thyroid function and cardiovascular events in patients with atrial fibrillation. Issue 3 (3rd August 2021) - Moutzouri, Elisavet; Lyko, Christina; Feller, Martin; Blum, Manuel Raphael; Adam, Luise; Blum, Steffen; Aeschbacher, Stefanie; Fischer, Urs; Roten, Laurent; Del Giovane, Cinzia; Meyer-Zuern, Christine S; Conte, Giulio; et al.
Abstract : Objective: To evaluate if subclinical thyroid dysfunction is associated with cardiovascular (CV) risk in patients with atrial fibrillation (AF). Methods: Swiss-AF is a prospective cohort of community-dwelling participants aged ≥ 65 years with AF. Primary outcome was a composite endpoint of CV events (myocardial infarctions, stroke/transitory ischemic events, systemic embolism, heart failure (HF) hospitalizations, CV deaths). Secondary outcomes were component endpoints, total mortality, and AF-progression. Exposures were thyroid dysfunction categories, TSH and fT4. Sensitivity analyses were performed for amiodarone use, thyroid hormones use, and competing events. Results: 2415 patients were included (mean age: 73.2 years; 27% women). 196 (8.4%) had subclinical hypothyroidism and 53 (2.3%) subclinical hyperthyroidism. Subclinical thyroid dysfunction was not associated with CV events, during a median follow-up of 2.1 years (max 5 years): age- and sex-adjusted hazard ratio (adjHR) of 0.99 (95% CI: 0.69–1.41) for subclinical hypothyroidism and 0.55 (95% CI: 0.23–1.32) for subclinical hyperthyroidism. Results remained robust following multivariable adjustment and sensitivity analyses. In euthyroid patients, fT4 levels were associated with an increased risk for the composite endpoint and HF (adjHR: 1.46, 95% CI: 1.04–2.05; adjHR: 1.70, 95% CI: 1.08–2.66, respectively, for the highest quintile vs the middle quintile). Results remained similar following multivariable adjustment and remained significant for HF in sensitivity analyses. No association between subclinical thyroid dysfunction and total mortality or AF-progression was found. Conclusions: Subclinical hypothyroidism was not associated with increased CV risk in AF patients. Higher levels of fT4 with normal TSH were associated with a higher risk for HF.